Prevalensi Retinopati Diabetik pada Penderita Diabetes Mellitus pada Komunitas Prolanis di Kota Mataram tahun 2018 - Monalisa Nasrul (Unram Medical Journal, 2021)
Background: Diabetic retinopathy (DR) is main cause of blindness in diabetic patients all over the world. Diabetic retinopathy prevalence in Asia is 10-43.1%. National data is not established yet. Awareness and early detection for diabetic retinopathy as an important part of preventing blindness remains low hence the possibility for increasing blindness due to diabetic retinopathy. Purpose: to measure diabetic retinopathy prevalence among diabetic patients in Prolanis community in Mataram. Metode: a cross-sectional descriptive study includes best corrected visual acuity, intra ocular pressure, anterior segment, funduscopy and fundus photo. Diagnosis of diabetic retinopathy is established based on ETDRS criteria, classified as non proliverative diabetic retinopathy (NPDR) and proliverative diabetic retinopathy (PDR). Funduscopy is examined by an ophthalmologist followed by fundus photo with or without dilating the pupils in an eye clinic in Mataram. Results: of 68 diabetic patients, there are 19 patients with diabetic retinopathy (28.36%). Those patients are mostly female, age 40-75 years old, diagnosed with diabetes for more than 10 years duration, have no complaints of blurred vision, best corrected visual acuity are better than 0.3 and have health insurance. Conclusion: prevalence of diabetic retinopathy in Prolanis community of diabetic patients in Mataram is 28.36%.